The Role of Islamic Social Finance in Muslim Countries: R-Biblioshiny Application - Zhulal; Aswad, Muhammad (International Journal of Waqf, 2024)
This bibliometric study discusses the current condition of documents about Islamic social finance documents published in journals equipped with digital object identifiers registered in the Scopus database. The analysis is focused on describing the characteristics and trends of keywords, authors and journals. Data analyzed from 59 research publications on scopus. The search keyword is "Zakat and Muslim Waqf". The search was used to establish the study dataset was last updated in January 2023. Descriptive statistical methods are used, and bibliometrix analysis is performed using biblioshiny, an R-based application, to generate bibliometrix maps. The number of articles discussing Islamic Social finance has increased considerably in recent months, with more than 50 articles published. The most popular keyword used with the topic of ISF (zakat and Waqf) is "Islamic", the second most common word is "Waqf", the third most common word is "Zakat". The related keywords are "Malaysia" then "philanthropy", "accounting, poverty, development, perspective, social, sharia". This study provides an overview of the trends of the most popular keywords, journals, and article authors on the topic of ISF (Zakat and Muslim Waqf), which has become quite popular in recent years, thus providing information for researchers who are concerned in this field.